The Determinants of Capital Structure of the GCC Oil and Gas Companies - Ahmed, Ibrahim Elsiddig; Sabah, Ariba (International Journal of Energy Economics and Policy, 2021)
This study aims to investigate the determinants of capital structure (CS), how they differ among levels (upstream, midstream, and downstream), and to identify Which CS theory is more relevant to the oil and gas companies in the GCC. It uses secondary data of 22 listed oil and gas companies in the GCC over ten years (2010 and 2019). The study will add to the literature as there is few studies about CS in the petroleum industry and it is the only study about the GCC oil and gas sector. Using pooled ordinary least square (OLS) random effect model, the main findings of this study are; the CS has a positive significant relationship with the size and tangibility, negative with profitability, and insignificant with growth in sales, market to book value, and price to earnings ratio. the research concluded that the GCC oil companies are aligned with both trade-off theory and pecking order theory. The results show that only the determinants of downstream companies are significant, while middle stream and upstream have no significant impact on CS. One of the limitations is unavailability of data of some governmental oil companies and further research is needed to include non-financial determinants and investigate relationships between CS and the value of companies. Keywords: Capital Structure Determinants; GCC Oil and Gas CS; CS Theory; Debt Asset Ratio; Debt Equity Ratio. JEL Classifications: G32; Q40, N75; L95 DOI: https://doi.org/10.32479/ijeep.10570